2015
DOI: 10.1002/pen.24183
|View full text |Cite
|
Sign up to set email alerts
|

A natural frequency approach to study the blown film helicoidal stability of HDPE bimodal resins and its relation to their rheological behavior

Abstract: A quantitative study of the helicoidal bubble stability (HBS) of five different HDPE bimodal resins processed under the same conditions was conducted to determine their natural frequencies and how these are related to molecular weight distribution features and typical viscoelastic data. The natural frequency x n , of each resin was obtained by representing the HBS phenomenon as an undamped system under the influence of a harmonic force, whose solution required force balance and Fourier series analyses of video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
(51 reference statements)
0
4
0
Order By: Relevance
“… Dimensionless temperature profile for blown film simulations of resin HDPE‐11 using the model and DSC data from Treviño‐Quintanilla …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… Dimensionless temperature profile for blown film simulations of resin HDPE‐11 using the model and DSC data from Treviño‐Quintanilla …”
Section: Introductionmentioning
confidence: 99%
“…A previous study, 10 using Cao and Campbel ls approach with a modified Phan-Thien-Tanner model, 9,11 included the crystallization constants obtained by normal DSC at different crystallization rates. This study showed that the DSC data are insufficient to simulate the blown film temperature profile for bimodal HDPE resins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PE is one of the most widely used thermoplastics and the highest-volume polymer in production and consumption. Its high toughness, ductility, excellent chemical resistance, low permeability and electrical conductivity, semicrystalline and ease of process make PE an attractive choice for various products and applications [ [1] , [2] , [3] , [4] ].…”
Section: Introductionmentioning
confidence: 99%